Study of the frequency of Hypomagnesemia in Hemodialysis patients using Proton Pump Inhibitors (PPI) (Medical Forum Monthly, 2024)
Objective: To study the frequency of Hypomagnesemia in Hemodialysis patients using Proton Pump Inhibitors (PPI) Study Design: Observational Study Place and Duration of Study: This study was conducted at the Idrees Teaching Hospital of Sialkot Medical College, Sialkot from January 2018 to January 2019. Materials and Methods: A total of 135patients were selected in Hemodialysis Unit, Idris teaching Hospital,Sialkot with proper written informed consent. Information was then collected using Performa.Participants were selected through non probability consecutive sampling technique. Samples for serum magnesium levels were taken immediately before dialysis. Serum magnesium levels were measured using photometric methods. Results: A total of 135 patients fulfilling the inclusion/exclusion criteria were enrolled in the study to calculate the frequency of hypomagnesemiain End Stage Renal Disease patients using PPI. Conclusion: We conclude that frequency of hypomagnesemia in hemodialysis patients using PPI is 79.3%.